2013
DOI: 10.1097/ta.0b013e31827e19a4
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric trauma patients are more likely to be discharged from the emergency department after arrival by helicopter emergency medical services

Abstract: Epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 8 publications
0
19
1
Order By: Relevance
“…HEMS have also been reported as being overused [ 8 , 12 ], sometimes being called for non-severe pediatric patients; therefore, it is not clear whether their effectiveness is only associated with patients with severe trauma. Moreover, HEMS cost more than GEMS [ 13 , 14 ], and staff require in-depth training concerning aviation and medical services [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…HEMS have also been reported as being overused [ 8 , 12 ], sometimes being called for non-severe pediatric patients; therefore, it is not clear whether their effectiveness is only associated with patients with severe trauma. Moreover, HEMS cost more than GEMS [ 13 , 14 ], and staff require in-depth training concerning aviation and medical services [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knofsky et al demonstrated that injured pediatric HEMS patients were both less severely injured and more likely to be discharged from the ED when compared to their adult counterparts. 42 …”
Section: Discussionmentioning
confidence: 99%
“…The hospital at which an injured child receives treatment typically has been governed by trauma triage protocols and criteria with high rates of over-triage and under-triage reported internationally [ 11 14 ]. In New South Wales (NSW), the study site, the most recent data suggest that less than one-third of severely injured children are initially treated at a Paediatric Trauma Centre (PTC) with a survival benefit between three and six times higher if treatment occurred at a PTC compared to those treated at an Adult Trauma Centre (ATC) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%